Natural Honey in the Management of Thermal Burn of the Foot in a Type 2 Diabetic Patient: A Case Report - Badryia Al-Lenjawi; Hashim Mohamed; Mansour Abu Salma; Zaghloul Abo Gouda (Dermatology, 2016)
We report the case of a 58-year old male with type 2 diabetes who was admitted to Um-Gwailinah Health Center with a second degree burn involving his big hallux, 4th and 5th toe and the bases of 2nd, 3rd, 4th and 5th toe of the right foot. The patient had sustained the second degree burn after exposing his right foot to hot charcoal during winter time in the desert. The patient reported loss of sensation in his feet which he described as being numb. He was diagnosed with type 2 diabetes thirty years ago and was suffering from hypertension, hypercholesterolemia and obesity. The patient divulged that he is a chronic heavy smoker with 40 cigarettes per day (i.e., 40 packs/year).